Mahishasuramardini sculpture - Temples of India Project Team (Jio Institute, 2024)
Draped in clothes the Mahishasuramardini sculpture is housed inside the garbhagriha (sanctum sanctorum) Mahishasuramardini Temple (Temple 9), Baroli group of temples.